Pendampingan Penyusunan AD/ART pada BUMDes Mitra Mandiri Desa Karangdoro Kecamatan Tegalsari Kabupaten Banyuwangi - Eko Budiywono (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Badan Usaha Milik Desa (BUMDes) are institutions that become the driving force of the community's economy, as well as BUMDes Mitra Mandiri Karangdoro Village, Tegalsari District, Banyuwangi Regency. Therefore, assistance is needed so that BUMDes provide benefits to the community. This assistance needs to be carried out considering that BUMDes Mitra Mandiri has never received assistance, especially in the preparation of AD/ART. The method used in this assistance is a service model with a PAR (Participatory Action Research) approach. From this assistance, it was concluded that assistance in the preparation of AD/ART is very necessary, considering that AD/ART is the basis for running BUMDes. In addition, the existence of BUMDes can support the improvement of the economy and the welfare of the community / village residents.